MATHEMATICS CREATIVE THINKING SKILLS INSTRUMENT TO SOLVE CUBE AND RECTANGULAR PRISM VOLUME PROBLEMS FOR ELEMENTARY SCHOOL STUDENTS - Aan Yuliyanto; Turmudi Turmudi; Ernawulan Syaodih; Arie Dharmawan; Cahya Karisma Pertiwi; Idat Muqodas; Dadan Rusdiana Saputra (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
Mathematical creative thinking skills can help students solve mathematical problems with diverse, unique, and detailed solutions and strategies. This study aims to produce an instrument capable of obtaining information about students' mathematical creative thinking skills to solve the cube and rectangular prism volume problems for elementary school students. Research and development are applied in this research. The population of this research was sixth-grade elementary school students in Jakarta and West Java. The participants were 33 students in East Jakarta and 15 students in Purwakarta. The sample is based on purposive sampling. The instrument developed was an essay test question. The item validity test shows that the three items are considered accurate for measuring mathematical creative thinking skills correctly. The instrument is considered consistent for measuring mathematical creative thinking skills and can measure mathematical creative thinking skills on similar subjects at different times and places. The difficulty level of the three items is moderate, so that belonging is not too difficult or easy. The discrimination power of the questions is very good to discriminate the skills of students who are classified as high and low. Thus, the mathematical creative thinking skills instrument can be used to understand the mathematical creative thinking skills of sixth-grade and can also be used to measure the mathematical creative thinking skills of fifth-grade elementary school students on the same material for further research.